Ototype Deteksi Banjir Menggunakan Platform Thinger.Io Dan Notifikasi Telegram - Romadoni, Dimas Aldi; Kalsum, Toibah Umi; Alamsyah, Hendri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Climate change and rapid urbanisation have increased the risk of flooding in various regions. Early detection systems are crucial to minimise material losses and casualties. This study aims to design and build an Internet of Things (IoT)-based flood detection prototype using the Thingr Io platform and Telegram notifications. The method used is a prototype, equipped with water level sensors that send real-time data to ThingeriO for monitoring and processing. If the data indicates a potential flood, the system automatically sends an alert to users via a Telegram bot so they can take preventive actions promptly. Testing showed that the system can detect water level increases with high accuracy and send notifications with a response time of approximately 5 seconds. At water levels of 128–168 cm, a red LED light indicates danger, while at 73–127 cm, a yellow LED light signals caution. and a green LED light indicates safety at water levels of 0-72 cm. This prototype is expected to become an effective and economical solution in supporting early warning systems for flood disasters across various regional scales.